The Anne of Green Gables storybook - McHugh, Fiona; McEwan, Rob; McLeod, William; Montgomery, L. M., (Lucy Maud), 1874-1942.; Ohashi, Rene (Buffalo, N.Y. : Firefly Books, 2007)
The story of an orphan who comes to stay at Green Gables. Illustrated with photos from the movie.
"Based on the Kevin Sullivan film of Lucy Maud Montgomery's classic novel, screenplay by Kevin Sullivan & Joe Wiesenfeld.".
6.5
4-6
5-8
Keywords: Country life -- Fiction; Friendship -- Fiction; Orphans -- Fiction; Country life -- Fiction; Friendship -- Fiction; Orphans -- Fiction; Prince Edward Island -- Fiction; Prince Edward Island -- Fiction